The Motherhood Wage Penalty and Its Determinants: A Public–Private Comparison. (21st July 2015) - Duvivier, Chloé; Narcy, Mathieu
Abstract: We investigate whether public and private sector employees bear a different wage penalty for having children. According to our estimates, the total motherhood wage penalty is much larger in the private than in the public sector. Nevertheless, in both sectors, we find no unexplained penalty once we control for potential determinants of the family pay gap, namely, a reduced labour supply of mothers, child‐related career interruptions, less access to management positions, and adjustments in working conditions. Finally, only child‐related career interruptions play a different role in explaining the motherhood wage penalty in each sector.